A reproducible endothelial-state contrast with limited bulk prognostic robustness in hepatocellular carcinoma - Si-yuan Tan; Lan-hui Qin; Wenqing Liang; Rui Song; Pei-yin Chen; Weihui Xu; Guanzhen Zeng; Yu Zhang; Liling Long (Functional & Integrative Genomics, 2026)

Toward advanced management of sludge bulking: An explainable evaluation framework to quantify and improve large language model cognitive capabilities - Boyan Xu; Ning Fan; Chuankun Zhang; Guangming Xu; Huarong Yu; Huabin Zeng; Rui Tong; Kaichang Yu; Zhiguo Yuan; How Yong Ng (Water Research, 2026)

Microplastics-induced effects on membrane fouling and effluent quality in MBRs for landfill leachate treatment under long-term operation - Shijie Bian; Jingwei Yan; Timing Jiang; Huying Li; Rui Cai; Wen Li; Jingjing Shi; Fan Yang; Sha Liang; Huabo Duan; Wenbo Yu; Shushan Yuan; et al. (Waste Management, 2026)

Microbiome dysbiosis and metabolic reprogramming in kiwifruit peel during Botrytis cinerea infection - Jingsheng Chen; Rui Ma; Yu Zhao; Yuan Sui; Zhuo Chen; Xianmei Xiao; Zhenshuo Wang; Jia Liu (Postharvest Biology and Technology, 2026)

Amplitude-controlled dynamic structural colors on wrinkling surfaces for facile multilevel strain-resolved optical encryption - Dengchong Feng; Shirui Wu; Yuxin Liu; Qi Guo; Rui Chen; Yu Chen; Yuzhao Yang; Haiqiang Wu; Zhiquan Zhao; Shaolin Lu; Zetong Ma; Cheng Wang; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Different drivers of active and inert carbon fraction on forest soil aggregate stability: a functional partitioning approach - Jing Lin; Rui Wang; Miao Xia; Jian-cong Zhang; Peng Qiu; Ke-xin Zhang; Bo Chang; Yu-lin Zhang; Tian-zi Xie; Yi Jian; Jia-yuan Wang; Shan-shan Guo (Journal of Soils and Sediments, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

Calcium-mediated catalytic ozonation for water purification: Synergistic interplay among surface acid-base sites, alkaline interfacial microenvironment and dynamic oxygen supplementation - Hong-Guang Li; Cheng Chen; Zhi-Hang Wu; Ai-Yong Zhang; Rui-Gang Zhang; Shao-Wei Yuan; Ming Du; Jing-Yu Zhang (Water Research, 2026)

Mechanistic insights into chromium immobilization and uptake inhibition in lettuce mediated by endophyte-loaded biochar - Qizhen Liu; Jie Yuan; Ziyan Fan; Ancao Pan; Qingfeng Zhang; Rui Zhou; Nazish Jabeen Abbasi; Chao Yu; Ying Feng (Journal of Hazardous Materials, 2026)

Genetic discrimination of the Dongshan Pb-Zn-Cu deposit based on sphalerite chemistry - Yi-Chen Chen; Shi-Jiong Han; Cheng-Gang Cao; Jun-Wei Bo; Yu-Rui Yuan; Ming-Yu Tang; Jin-Xin Yuan (Journal of Geochemical Exploration, 2026)

A heterotrophic nitrification and aerobic denitrification strain capable of antibiotic degradation: From function to mechanism - Jia-Ying Li; You-Wei Cui; Yuan Sui; Ji-Tao Yan; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Ze-You Lu (Environmental Pollution, 2026)

Genetic dissection of a key dynamic growth period QTL for source–sink-related traits and its breeding application potential in wheat - Meng Yuan; Hongke Ding; Yunkai Yue; Chuanliang Zhang; Yuze Wang; Dandan Zhang; Shipeng Li; Ruiqi Nie; Jia Liu; Yanchuan Huang; Jinyu Han; Sufu Deng; et al. (Theoretical and Applied Genetics, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Spatial and environmental niche differentiation facilitates sympatric macaques' coexistence in montane-canyon landscapes: Implications for conservation - Wei Zhou; Yuan Wang; Deyan Ge; Qisen Yang; Gang Song; Jilong Cheng; Tian Tian; Yu Zhang; Jinbo Xu; Ying Liu; Weibo Wang; Xiaochuan Wang; et al. (Biological Conservation, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

ERK1/2 activation in anti-inflammatory effects and underlying signaling mechanisms - Kaiwen Tao; Lin Xu; Chao Cheng; Fukang Yuan; Yicheng Yu; Lidan Zhang; Runmin Li; Rui Xia; Haibei Dong; Xingqi Wang (Inflammation Research, 2026)

Lignin-based sunscreen materials: A review of mechanisms of action, precision modification strategies, multifunctional application advances, challenges and prospects - Yuan Chen; Zibo Yu; Rui Tang; Jiayi Sun; Xigao Jian; Jinyan Wang; Xiaozhou Zhang; Xing Wang; Jingyu Xu (Journal of Environmental Chemical Engineering, 2026)

Hydrogenophaga pseudoflava widely distributed in wastewater treatment plants exhibiting heterotrophic nitrification-aerobic denitrification: From characterization to genomics - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Jia-Ying Li; Ya-Nan Mi; Xin-Yu Gu (Bioresource Technology, 2026)

Do gender differences affect the sustainable intensification of cultivated land use among farming households?--evidence from Shenyang, China - Xiao Lyu; Yuan Liu; Wenlong Peng; Rui Yu (Journal of Rural Studies, 2026)

Physicochemical properties, antioxidant activity, antibacterial properties, and fruit preservation potential of black soldier fly chitosan films - Bin-Qiao Yuan; Ting-Hao Yu; Jun-Kui Huang; Xin-Rui Ren; Run-Jia Wang; Guo-Xin Huang; Nortoji A. Khujamshukurov; Da-Wei Huang; Jin-Hua Xiao (Food Bioscience, 2026)

Plasma organophosphate ester exposure-associated microRNA expression profiles and their functional analysis in Chinese healthy adults - Xulin Zhang; Zirui Zhang; Yuxin Xu; Jiajia Zhu; Guang Chen; Rui Zeng; Wending Li; Xuedan Xu; Yu Yuan; Tao Jing; Tangchun Wu; Pinpin Long (Environmental Research, 2026)

Incorporating Thermal Adaptation and Acclimation Improves Light‐Use Efficiency Modeling for Estimating Gross Primary Production in Tibetan Plateau Grasslands - Gaofei Yin; Jiangliu Xie; Yu Wang; Rui Chen; Yajie Yang; Dujuan Ma; Wenping Yuan; Qiaoyun Xie; Da Wei; Huai Chen; Xinwei Liu; Aleixandre Verger; et al. (Global Change Biology, 2026)
The optimal temperature for photosynthesis (Topt), the temperature at which photosynthesis peaks, is crucial for estimating gross primary production (GPP). Most models, however, apply biome‐specific Topt, overlooking the spatial and temporal variability driven by the genetic adaptation and interannual thermal acclimation of plants, thus introducing systematic error in GPP estimation. We mapped Topt of Tibetan Plateau (TP) grassland averaged over 1982–2018, using satellite‐derived near‐infrared reflectance of vegetation as a proxy of photosynthesis, and projected future Topt under different scenarios of shared socioeconomic pathways (SSPs) using space‐for‐time substitution. We assessed the effects of Topt adaptation on current GPP estimation and acclimation on projected GPP using a light‐use efficiency model (i.e., EC‐LUE model). The spatial heterogeneity of Topt was pronounced across the TP grassland, with higher values in the northeast and lower values in the southwest, averaging 9.32°C ± 3.15°C. Topt tended to increase from 2040 to 2080 across all SSPs, with the slowest increase under SSP1‐2.6 (0.015°C y −1 ) and the fastest increase under SSP5‐8.5 (0.061°C y −1 ). Incorporating Topt adaptation into the EC‐LUE model improved the accuracy of GPP estimation, with R 2 increasing by 7.19% and RMSE decreasing by 11.40%, compared to the model with a fixed Topt. In contrast, ignoring the adaptation of Topt led to systematically lower GPP values across 77.9% of the TP grassland, resulting in an overall reduction of estimated GPP by 7.07% (0.07 g C m −2 d −1 ). Ignoring the acclimation of Topt led to systematically higher projected GPP on the TP, ranging from 2.87% ± 8.96% (SSP1‐2.6) to 3.83% ± 5.97% (SSP3‐7.0) across different scenarios, covering more than 70% of TP regions. These findings highlight the necessity of incorporating both the adaptation and acclimation of Topt into GPP models to enhance the monitoring of the carbon cycle.

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Driving factors on bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants: Evidence from different latitudinal gradients in warm season - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Yuan Sui; Tong Ren; Xin-Yu Gu; Ming-Xin Su; Ze-You Lu (Journal of Water Process Engineering, 2026)

Identification of microplastics in landfill leachate: An underestimated tiny microplastics using Focal Plane Array (FPA)-based Fourier Transform Infrared (FTIR) imaging - Shijie Bian; Timing Jiang; Jingwei Yan; Rui Cai; Shushan Yuan; Wenbo Yu; Sha Liang; Liang Huang; Huabo Duan; Mukesh Kumar Awasthi; Jiakuan Yang (Journal of Environmental Sciences, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Establishment and application of multiple cross displacement amplification coupled with lateral flow biosensor (MCDA-LFB) for visual and rapid detection of Candida glabrata - Yan Yuan; Yuhong Zhou; Yanfeng Zhou; Rui Ye; Jingrun Lu; Yizhe Wang; Fang Wei; Fukuan He; Honglan Yu; Yu Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Static magnetic field coupled with control of sludge retention time enhancing nitrogen removal via heterotrophic nitrification-aerobic denitrification - Ming-Xin Su; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Xin-Yu Gu; Jia-Ying Li; Ze-You Lu (Journal of Water Process Engineering, 2026)

The impact of precipitation and exposed rocks on the soil and water leakage processes in the karst depressions-sinkhole system: Insights from a laboratory simulation experiment - Feiyang Cai; Rui Li; Jiang Yuan; Benjin Yu (Soil and Tillage Research, 2026)

Alkalinity change induces succession of heterotrophic and autotrophic nitrifying bacterial communities: Comprehensive insights on the mechanism - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Ya-Nan Mi; Xin-Yu Gu; Jia-Ying Li; Ming-Xin Su (Journal of Environmental Management, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

Sustainable production of Microalgae-Derived turbostratic graphene via flash Joule heating - Fuyuan Wang; Rui Huang; Yujie Yu; Shaojunyan Tan; Ruijie Yuan; Jianyong Yin; Shijie Zhang (Bioresource Technology, 2026)

Structural characterisation of a novel polysaccharide from pseudostellaria heterophylla fibrous root and its anti-inflammatory and antioxidant activities in vitro - Meng-Yu Li; Hai-Tian Deng; Ming-Zhu Ye; Li-Li Lu; Hong-Yuan Chen; Wen Rui (Natural Product Research, 2026)

Enhancement role of corncob slow-release carbon source on heterotrophic nitrification and aerobic denitrification process in low C/N wastewater treatment - Xin-Yu Gu; You-Wei Cui; Yuan Sui; Jia-Ying Li; Ming-Xin Su; Ze-You Lu; Rui-Chun Yang (Journal of Environmental Management, 2026)

An empirical study on the thermal environment improvement and energy conservation of high-reflective-evaporative composite roofs - Lina Jiang; Yunran Min; Jihui Yuan; Chaoqun Zhuang; Rui Guo; Jiayao Yu; Yafeng Gao (Building and Environment, 2026)

Development of an environmentally sustainable composite incorporating phosphogypsum aggregate: a perspective for enhancing interfacial stability - Shiyuan Fu; Chiqiu Wu; Wei Lv; Yuan Feng; Xue Liu; Yuxin Zhou; Kangning Liu; Rui Yu (Innovative Infrastructure Solutions, 2026)

Dynamic characteristics of a novel floating offshore photovoltaic system with flexible rope-net connection - De-Qing Zhang; Hong-Wei Tian; Zhi-Ming Yuan; Shuang-Rui Yu; Jun-Feng Du; Hua-Jun Li (Ocean Engineering, 2025)

Atmospheric and room-temperature plasma mutagenesis enhances the tolerance of Arthrospira platensis to photoinhibition and high-CO2 levels - Ruolan Yuan; Chunli Yu; Rui Xu; Jin Liu; Lina Zhou; Shengxi Shao; Jun Qian; Jingjing Li; Peilun Xu; Wenguang Zhou (Chemical Engineering Journal, 2025)

Trace polymer additive-mediated H-bond reconstruction and water-deficient Helmholtz layer for 4500 h Zn anodes - Huijie Li; Zichun Yuan; Leyao Li; Qiang Yu; Fuxin Wang; Rui Li; Yanxia Yu; Dezhou Zheng; Xihong Lu (Chemical Engineering Journal, 2025)

Hydrodynamic characteristics of horizontal-axis tidal turbine with Gurney Flap and vortex generators - Yonghui Liu; Yuqi Liu; Yu Xue; Junzhe Tan; Peng Yuan; Xiancai Si; Zhen Pei; Rui Shu; Xiaodong Liu (Ocean Engineering, 2025)

Efficient synthesis of FePO4 from the incinerated sewage sludge ash by modification–selective leaching–precipitation - Zhong-hua Yang; Chuan-ming Du; Pei-yuan Ni; Lei Yuan; Yu-tang Zhang; Rui-yuan Yuan (Chemical Engineering Journal, 2025)

Nine years of grazing and fertilization shape dynamics of soil phosphorus fractions in Karst pasture ecosystems - Wangfei Qin; Rui Dong; Xinyao Gu; Shaokun Hu; Song Cui; Xuechun Zhao; Jihui Chen; Yinglai Shi; Chao Chen; Yuan Li; Narasinha Shurpali; Mikko Järvinen; et al. (Agriculture, Ecosystems & Environment, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Flavonoids as Signals Mediate Plant-nematode Communication Through Regulating Nematode Perceptual Ability - Xiang-Yu Zhang; Rui Yuan; Yaseen Ullah; Xu-Dong Li; Hao-Ran Li; Wei Zhang (Journal of Chemical Ecology, 2025)

Research progress on programmed cell death of cardiomyocytes in pressure-overload hypertrophic cardiomyopathy - Fei Xiao; Hui-Li Li; Jia-Rui Wang; Hui-Min Wu; Yu-Qi Cai; Jia-Wan Wang; Hao Che; Gang Li; Zheng-Yuan Xia; Yu-Bo Xie; Sheng Wang (Apoptosis, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

Identification and characterization of a new strain of Ictalurid herpesvirus 1 isolated from channel catfish in China - Fei Yu; Jiehua Xu; Sheng Yuan; Yi Yang; Siyang Song; Kai Hao; Rui Yuan; Yu Wang; Xiaohui Chen; Zhe Zhao (Aquaculture, 2025)

Genome-wide association and epidemiological evidence linking air pollution to aging mechanisms - Xiao-Yu Liu; Dong Peng; Xu-Rui Liu; Yuan-Hui Sheng; Jun-Nan Zhao; Rong-Bin Xu; Dan Zhang; Bo Chen (Journal of Hazardous Materials, 2025)

Transmembrane uptake of polystyrene nanoplastics mediated by aquaporin in tartary buckwheat: Physiological consequence and genomic mechanism - Yu-Kang Hou; Shuo Gao; Qiang Lai; Wen-Rui Lu; You-Bao Cai; Ya-Wen Yuan; Si-Yuan Yao; Hong-Yan Tao; Li-Zhe An; You-Cai Xiong; Yuan Song (Journal of Hazardous Materials, 2025)

Inactivation of Penicillium spp. in apple juice by pulsed light and the exploration of its mechanisms - Guolong Li; Saiqun Wang; Yu Li; Lu Cui; Rui Cai; Tianli Yue; Yahong Yuan; Zhouli Wang (Food Control, 2025)

Two alkenyl phenol derivatives from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Jing Tang; Rui Xu; Hao Ma; Shuai-Ming Zhu; Fu-Yao Luo; Xue Zhao; Ya-Shuai Kang; Yuan-Wei Gao; Yu Yang; Chang-Wei Li (Natural Product Research, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Virus communities rather than bacterial communities contribute more on nutrient pool in polluted aquatic environment - Qiaoling Yu; Xueqian Hu; Yuan Qian; Yu Wang; Chenwei Shi; Rui Qi; Petr Heděnec; Zhibiao Nan; Huan Li (Journal of Environmental Sciences, 2025)

Adaptive neofunctionalization of ancestral CYP6SN2vB following duplication contributes to abamectin resistance in Chilo suppressalis Walker - Shuai Wang; Yuan Xie; Chong Liu; Jin-Wei Liu; Fang-Rui Guo; Song-Tao Qiao; Yu-Ji Xing; Shun-Fan Wu; Chris Bass; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2025)

Electroacupuncture may alleviate inflammatory pain by downregulating the expression of P2Y14 receptor in the primary somatosensory cortex - Shuai Hou; Cui-Yuan Chen; Rui-Zhu Zhou; Liu-Xuan He; Xiao-Xiao Zhao; Sha-Sha Chen; Sha Yang; Hai-Yan Yin; Shu-Guang Yu (Purinergic Signalling, 2025)

Responses of an invasive plant Alternanthera philoxeroides to cadmium, nutrient availability and water temperature - Zi-Yang Xie; Zhi-Hang Liu; Xin-Yue Gu; Yuan-Yuan Qin; Yu-Ting Du; Jin Yan; Rui Zhang; Chao Si (Aquatic Botany, 2025)

The long noncoding RNA VIVIpary promotes seed dormancy release and pre-harvest sprouting through chromatin remodeling in rice - Lu Yang; Yu Cheng; Chao Yuan; Yan-Fei Zhou; Qiao-Juan Huang; Wen-Long Zhao; Rui-Rui He; Jie Jiang; Yi-Chao Qin; Zheng-Tong Chen; Yu-Chan Zhang; Meng-Qi Lei; et al. (Molecular Plant, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Metabolic and ecological responses of denitrifying consortia to different carbon source strategies under fluctuating C/N conditions - Rui-Zhe Sun; Yuan Pan; Jun Wang; Tong Gao; Han-Qing Yu; Jin Wang (Environmental Research, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Bacterial cellulose-based Pickering emulsions reinforced with silver and silica nanoparticles for advanced antibacterial and hydrophobic food packaging solutions - Qimin Chen; Fan Yang; Yalong Hou; Zhiyang Li; Di Yuan; Chao Liu; Feihong Hu; Rui Zhao; Huili Wang; Wenxia Liu; Fengshan Zhang; Qiang Wang; et al. (Carbohydrate Polymers, 2025)

Selective preparation of aromatic compounds from catalytic pyrolysis polyester coating over Ni, Mo and Co metal modified ZSM-5 - Zhen-Qiang Yu; Yao-Xin Xiao; Dong Liang; Che Zhao; Zhen Huang; Gang-Qi Cheng; Rui Shan; Hao-Ran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Biochar-supported Fe₃O₄ nanoparticles affects bacterial community diversity and phosphorus speciation transformation during pig manure aerobic composting by generating hydroxyl radicals and hydrogen peroxide - Ning Yuan; Kang Wang; Jia Zhou; Nana Luo; Rui Yu (Journal of Environmental Chemical Engineering, 2025)

Advancing antibiotic detection and degradation: recent innovations in graphitic carbon nitride (g-C3N4) applications - Rui Liu; Chaojun Zhang; Rijia Liu; Yuan Sun; Binqiao Ren; Yuhang Tong; Yu Tao (Journal of Environmental Sciences, 2025)

The research on the synergistic improvement of water retention capacity and eating quality of marinated pork meat by the combination of basic arginine and acidic aspartic acid - Kuo Xu; Ao-Jing Lv; Rui-Ling Dong; Yu-Cong Li; Li-Ting Zeng; Yang Wang; He-Shuai Li; Jun Qi; Hu-Hu Wang; Chun-Hui Zhang; Guo-Yuan Xiong; Qing-Yong Zhang (Food Chemistry, 2025)

Fruit wines classification enabled by combing machine learning with comprehensive volatiles profiles of GC-TOF/MS and GC-IMS - Changlin Zhou; Yashu Yu; Jingya Ai; Chuan Song; Zhiyong Cui; Quanlong Zhou; Shilong Zhao; Rui Huang; Zonghua Ao; Bowen Peng; Panpan Chen; Xiaoxiao Feng; et al. (Food Research International, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

The Impact of Different Mating Systems on Locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Ruo-Xi Wang; Jia-Xin Xu; Kai-Chen Weng; An-Xin Wang; Hao Huang; Yu-Yuan Lu; Yi-Jie Chen; Yu-Chen Wang (Journal of Insect Behavior, 2025)

Efficient photothermal conversion and Z-scheme charge transfer in narrow-gap semiconductor heterojunction for photothermal-assisted photocatalysis - Yu-Ting Chen; Wen-Xi Xia; Yuan Zhou; Qi-Rui Zhang; Xiang-Bai Chen; Liang Ma; Si-Jing Ding (Journal of Environmental Chemical Engineering, 2025)

The long noncoding RNA ALEX1 confers a functional phase state of ARF3 to enhance rice resistance to bacterial pathogens - Meng-Qi Lei; Rui-Rui He; Yan-Fei Zhou; Lu Yang; Zhen-Fei Zhang; Chao Yuan; Wen-Long Zhao; Yu Cheng; Jian-Ping Lian; Yu-Chan Zhang; Wen-Tao Wang; Yang Yu; et al. (Molecular Plant, 2025)

Effective removal of Pb from industrial wastewater: A new approach to remove Pb from wastewater based on engineered yeast - Hao Luo; Zheng Su; Yang Liu; Dong-Fang Yuan; Rui Wang; Yu-Hang Ning; Dong-Jiao Zhang; Xian-Ke Chen; Zhao-Bao Wang; Xue-Yan Gao; Yue-Chao Zhang; Guang Cheng; et al. (Journal of Hazardous Materials, 2025)

Alleviates effects of γ-cyclodextrin/genistein inclusion complex on oxidative stress injury induced by organic hydrogen peroxide in PC12 cells via Nrf2/GPx4 signaling pathway - Mengmeng Zhang; Jingbo Liu; Yiding Yu; Wenshuo Ren; Rui Yuan; Xuanting Liu; Xiaomin Shang; Zhiyang Du; Meng-Lei Xu; Ting Zhang (Food Bioscience, 2025)

Tracking cement transportation carbon emissions in China: Historical assessment and future simulation - Rui Li; Yuchen Wei; Weiguang Cai; Yuan Liu; Kairui You; Yanhui Yu (Environmental Impact Assessment Review, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Efficient resource recovery from food waste digestate via hydrothermal treatment and its application as organic fertilizer - Hong Chen; Jun Sheng; Qinhui Ye; Jun Li; Xin Yu; Hanyue Wu; Rui Zhang; Shiyi Zhao; Xiaoming Zou; Xiang Li; Gang Xue; Baoling Yuan (Bioresource Technology, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Contribution of alkaline magmas to the petrogenesis of Triassic aluminous A-type granites on Liaodong Peninsula, Northeastern China - Yu-Sheng Zhu; Jin-Hui Yang; Jin-Feng Sun; Jing-Yuan Chen; Lei Xu; Rui Li; Bao-Quan Zhou (Lithos, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Green fabrication of modified lignin/zeolite/chitosan-based composite membranes for preservation of perishable foods - Zhan-Chao Li; Meng-Yao Su; Xiao-Yu Yuan; Hai-Qing Lv; Rui Feng; Li-Jie Wu; Xiao-Ping Gao; Yan-Xia An; Zhan-Wei Li; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Chemistry, 2024)

Sirtuin 7 ameliorates cuproptosis, myocardial remodeling and heart dysfunction in hypertension through the modulation of YAP/ATP7A signaling - Yu-Fei Chen; Rui-Qiang Qi; Jia-Wei Song; Si-Yuan Wang; Zhao-Jie Dong; Yi-Hang Chen; Ying Liu; Xin-Yu Zhou; Jing Li; Xiao-Yan Liu; Jiu-Chang Zhong (Apoptosis, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Peering through the hedge: Multiple datasets yield insights into the phylogenetic relationships and incongruences in the tribe Lilieae (Liliaceae) - Deng-Feng Xie; Juan Li; Jia-Hui Sun; Rui-Yu Cheng; Yuan Wang; Bo-Ni Song; Xing-Jin He; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Zirconium based metal–organic frameworks with aggregation-induced electrochemiluminescence for sensitive analysis of aflatoxin B1 by signal dual-amplification strategy - Yuan Li; Xue Dong; Tingting Wu; Xiaoyue Zhang; Xiang Ren; Rui Feng; Yu Du; Jin Yong Lee; Xuejing Liu; Qin Wei (Chemical Engineering Journal, 2024)

Phthalates on indoor surfaces and associated exposure via surface touch behavior: Observation in university dormitories and its implications - Fangzhou Yuan; Yu Sun; Na Li; Jianping Cao; Nan Zhang; Daniel Mmereki; Zhonghua Wei; Rui Chen; Jinyu Zhou; Yousheng Xu; Zhongming Bu (Building and Environment, 2024)

Yr29 combined with QYr.nwafu-4BL.3 confers durable resistance to stripe rust in wheat cultivar Jing 411 - Mingjie Xiang; Bo Tian; Jianghao Cao; Shengjie Liu; Caie Zhou; Xiaoting Wang; Yibo Zhang; Jiale Li; Xunying Yuan; Jufen Wan; Rui Yu; Weijun Zheng; et al. (Theoretical and Applied Genetics, 2024)

Soil organic phosphorus is mainly hydrolyzed via phosphatases from ectomycorrhiza-associated bacteria rather than ectomycorrhizal fungi - Jing Yuan; Rui Yan; Xueqiong Zhang; Kai Su; Hui Liu; Xin Wei; Ran Wang; Lanlan Huang; Nianwu Tang; Shanping Wan; Wei Liu; Hans Lambers; et al. (Plant and Soil, 2024)

Exploring the gradient impact of climate and economic geographical factors on city-level building carbon emissions in China: Characteristics and enlightenments - Rui Li; Yanhui Yu; Weiguang Cai; Yuan Liu; Yan Li (Sustainable Cities and Society, 2024)

Exploration of hydrogen-rich gas evolution mechanism during vitrinite pyrolysis: A combined TG-MS and ReaxFF study - Yuan-Yuan Jiang; Jie-Ping Wang; Jin-Xiao Dou; Rui Guo; Li-Hua Fan; Guang-Yue Li; Ying-Hua Liang; Jiang-Long Yu (Fuel, 2024)

Suppression the glucose-induced ferroptosis in endothelial cells by 4OI-loading exosomes hydrogel for the treatment of diabetic foot ulcer - Kuo Shen; Rui Zheng; Bangrui Yu; Hao Zhang; Peng Wang; Peng Zhao; Jijun Chen; Yixuan Yuan; Yuhang Wang; Kejia Wang; Yanhui Jia; Ruizhi Wang; et al. (Chemical Engineering Journal, 2024)

Enhancing reaction kinetics in aprotic magnesium-air batteries using a freestanding flexible metal-free carbon fiber cathode - Wenbo Liu; Ning Wang; Rui Zhong; Fanfan Liu; Yongjun Wu; Qianyi Zhang; Xiaoyan Chen; Yanmei Li; Minghui Yu; Rui Xu; Yifei Yuan; Dan Luo; et al. (Chemical Engineering Journal, 2024)

Mechanisms for carbon stock driving and scenario modeling in typical mountainous watersheds of northeastern China - Jin Zhang; Wen-Guang Zhang; Xin-Yan Zhang; Yu-Hong Li; Ming-Ming Feng; Peng Qi; Yi-Qiang Huang; Rui Li; Ming Jiang; Yuan-Chun Zou; Yi Wu (Environmental Monitoring and Assessment, 2024)

MARCH1 and MARCH2 inhibit pseudorabies virus replication by trapping the viral cell-to-cell fusion complex in trans-Golgi network - Rui Huang; Cui-Hong Rao; Yuan-Zhe Bai; Changqing Yu; Meng Chen; Jin-Mei Peng; Shi-Jia Xu; Yue Sun; Meng Fandan; Chuang Lyu; Mirwaise Khan; Tong-Qing An; et al. (Veterinary Microbiology, 2024)

Effect of tunnel ventilation on surrounding rock temperature field and heat regulating circle during construction phase - Ming-Rui Luo; Yu-Chun Tao; Zuo-Bing Yuan; Liang-Liang Tao; Chuan He; Yan-Ping Yuan; Xiao- Yu Tian; Yan-Hua Zeng (Tunnelling and Underground Space Technology, 2024)

Optimal declutching control of hinged multiple floating bodies - Shuang-Rui Yu; Ming Zhang; De-Qing Zhang; Zhi-Ming Yuan (Ocean Engineering, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Self-reporting electroswitchable colorimetric platform for smart ammonium recovery from wastewater - Rui Wei; Chi Ding; Yuan Yu; Chaomeng Wei; Jinna Zhang; Nanqi Ren; Shijie You (Water Research, 2024)

Quercetin regulates dendritic cell activation by targeting STAT4 in the treatment of experimental autoimmune encephalomyelitis - Fang Zhou; Yu-Xin Guo; Rui Gao; Xiao-Yu Ji; Yu-Xuan Tang; Li-Bin Wang; Yuan Zhang; Xing Li (Toxicology and Applied Pharmacology, 2024)

Model predictive control of wave energy converters - Ming Zhang; Shuang-Rui Yu; Guang-Wei Zhao; Sai-Shuai Dai; Fang He; Zhi-Ming Yuan (Ocean Engineering, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

Two new sesterterpenoids from Atractylodes japonica Koidz. ex Kitam - Yuan-Yuan Zhou; Zhao Sun; Yan Liu; Zhen-Xing Fang; Hui-Rui Gao; Ning-Yu Liu; Xiao-Juan Zhang; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2024)

Genome-wide identification and expression-pattern analysis of sulfate transporter (SULTR) gene family in cotton under multiple abiotic stresses and fiber development - Yu Chen; Xianghui Xiao; Rui Yang; Zhihao Sun; Shuhan Yang; Haibo Zhang; Baoguang Xing; Yanfang Li; Qiankun Liu; Quanwei Lu; Yuzhen Shi; Youlu Yuan; et al. (Functional & Integrative Genomics, 2024)

Phosphorus recovery from phosphate tailings through a two-stage leaching-precipitation process: Toward the harmless and reduction treatment of P-bearing wastes - Yao-hui Yu; Chuan-ming Du; Yu-tang Zhang; Rui-yuan Yuan (Environmental Research, 2024)

The carbon dots with near-infrared electrochemiluminescence emission and low excitation potential for ultrasensitive analysis of microRNA-222 - Yu-Zhuo Guo; Rui Liu; Ying Zeng; Ye-Yu Liao; Jia-Li Liu; Ya-Qin Chai; Ruo Yuan (Chemical Engineering Journal, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Study on physiological and biochemical characteristics during in vitro flowering of Rosa ‘Yametsu-Hime’ - Meijing Yuan; Shengdie Weng; Yu Ma; Rui Wu; Xiaoling Kang; Li Du (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Heat stress enhances the occurrence of erythromycin resistance of Enterococcus isolates in mice feces - Lingxian Yi; Rui Xu; Xiaowu Yuan; Zining Ren; Huihui Song; Huamin Lai; Zhihua Sun; Hui Deng; Bo Yang; Daojin Yu (Journal of Thermal Biology, 2024)

HNF4A as a potential target of PFOA and PFOS leading to hepatic steatosis: Integrated molecular docking, molecular dynamic and transcriptomic analyses - Rui Li; Zijing Zhang; Yuxin Xuan; Yulu Wang; Yuyan Zhong; Lingyin Zhang; Jinrui Zhang; Qian Chen; Shuling Yu; Jintao Yuan (Chemico-Biological Interactions, 2024)

Evaluation on 131I production based on molten salt reactor off-gas extraction - Liang Chen; Liao-Yuan He; Bo Zhou; Gui-Feng Zhu; Yu-Han Fan; Hong-Jie Xu; Rui Yan; Yang Zou (Annals of Nuclear Energy, 2024)

Significant methane ebullition from large shallow eutrophic lakes of the semi-arid region of northern China - Linxiang Zhang; Xiangwei Li; Ruihong Yu; Yue Geng; Liangqi Sun; Heyang Sun; Yuan Li; Zhonghua Zhang; Xiangyu Zhang; Xue Lei; Rui Wang; Changwei Lu; et al. (Journal of Environmental Management, 2023)

Peripheral BDNF Regulates Somatosensory–Sympathetic Coupling in Brachial Plexus Avulsion-Induced Neuropathic Pain - Hang Xian; Huan Guo; Yuan-Ying Liu; Jian-Lei Zhang; Wen-Chao Hu; Ming-Jun Yu; Rui Zhao; Rou-Gang Xie; Hang Zhang; Rui Cong (Neuroscience Bulletin, 2023)

Low-dose IL-2 Treatment Rescues Cognitive Deficits by Repairing the Imbalance Between Treg and Th17 Cells at the Middle Alzheimer’s Disease Stage - Lin Yuan; Lei Xie; Hao Zhang; Yu Zhang; Yunbo Wei; Jinhong Feng; Li Cui; Rui Tian; Jia Feng; Di Yu; Cui Lv (Journal of Neuroimmune Pharmacology, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Ferrostatin-1-loaded thermosensitive nanodelivery system for noise-induced hearing loss treatment - Peng-Wei Ma; Pei-Heng Lu; Hao Yuan; Jia-Wei Chen; Wei Gao; Yu-Qiang Lun; Jia-Ning Guo; Xue-Rui Ding; Rui Liang; Si-Yu Li; Zi Wang; Wei-Long Wang; et al. (Chemical Engineering Journal, 2023)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

Demethylation-Driven ligase chain reaction for simultaneously sensitive detection of m6A demethylase FTO and m1A demethylase ALKBH3 in breast cancer at Single-Molecule level - Ming-hao Liu; Qian Zhang; Wan-tong Yu; Jian-Ge Qiu; Hui-min Yuan; Chuan-rui Wang; Bing-Hua Jiang; Yan Zhang; Chun-yang Zhang (Chemical Engineering Journal, 2023)

Transient, printable and recyclable gelatin hydrogels with enhanced mechanical sensing and electromagnetic shielding performance by incorporation of reduced graphene oxide - Rui Yin; Chen Zhang; Youyou Chen; Yu Wang; Qiang Feng; Yaming Liu; Minghan Yu; Yunhuan Yuan; Cheng-Yan Xu; Feihua Liu; Weiwei Zhao (Chemical Engineering Journal, 2023)

Dietary acetate promotes growth and nutrients deposition in Nile tilapia (Oreochromis niloticus) through increasing acetyl-CoA-triggered energy production - Wen-Hao Zhou; Samwel M. Limbu; Yuan Luo; Rui-Xin Li; Jiong Ren; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Aquaculture, 2023)

Rapid determination of the relative configuration of diverse 8,4′-oxyneolignans by NMR analysis: Retrospective studies, improvement and structural revision - Peng Zhao; Li-Li Lou; Ben-Song Xin; Zhi-Yuan Li; Rui Guo; Wei-Yu Zhou; Tian-Ming Lv; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Time-optimal path planning and tracking based on nonlinear model predictive control and its application on automatic berthing - Ming Zhang; Shuang-Rui Yu; Kwang Sic Chung; Ming-Lu Chen; Zhi-Ming Yuan (Ocean Engineering, 2023)

Direct immobilization of Se(IV) from acidic Se(IV)-rich wastewater via ferric selenite Co-precipitation - Zidan Yuan; Rui Su; Xu Ma; Le Yu; Yuanming Pan; Ning Chen; Roman Chernikov; Leo Ka Long Cheung; Reza Deevsalar; Ayetullah Tunc; Liang Wang; Xiangfeng Zeng; et al. (Journal of Hazardous Materials, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Synchronous regulation of Schottky/p-n dual junction in Prussian blue-derived Janus heterostructures: A path to ultrafast long life potassium ion batteries - Shou-Shan Mai; Kai-Yuan Hsiao; Yi-Chun Yang; Ying-Rui Lu; Ming-Yen Lu; Yi-Yen Hsieh; Che-Bin Chang; Hsing-Yu Tuan (Chemical Engineering Journal, 2023)

Flat-leaf submerged plants are more sensitive to invasion intensity and water nutrition levels than needle-leaf ones - Yi-Luan Shen; Shu-Yu Zhang; Xiao-Fei Yuan; Kai Sun; Jing-Fang Cai; Jing-Jing Xue; Yu Zhang; Si-Ha A; Li-Juan Yang; Rui Cheng; Hong-Li Li; Guang-Chun Lei (Hydrobiologia, 2023)

Comparative transcriptome profiling reveals RNA splicing alterations and biological function in patients exposed to occupational noise - Jia-Wei Chen; Jun-Jie Shao; Shao-Fei Zhao; Pei-Heng Lu; Si-Yu Li; Hao Yuan; Peng-Wei Ma; Yu-Qiang Lun; Wei-Long Wang; Rui Liang; Wei Gao; Qian Yang; et al. (Environmental Science and Pollution Research, 2023)

Carbon source shaped microbial ecology, metabolism and performance in denitrification systems - Yuan Pan; Rui-Zhe Sun; Yan Wang; Guan-Lin Chen; Ying-Ying Fu; Han-Qing Yu (Water Research, 2023)

Comprehensive understanding of tetracycline hydrochloride adsorption mechanism onto biochar-based gel pellets based on the combination of characterization-based and approximate site energy distribution methods - Bai-Qin Zhou; Qian-Qian Sang; Yu-Jun Wang; Hui Huang; Fang-Jun Wang; Rui-Chun Yang; Yuan-Tian Zhao; Zi-Jie Xiao; Chun-Yue Zhang; Hui-Ping Li (Journal of Cleaner Production, 2023)

Phylogenetic analysis and molecular characterization of the co-infection of the new variant of the porcine epidemic diarrhea virus and the novel porcine kobuvirus isolated from piglets with diarrhea - Ran Wei; Rui Shang; Kaihui Cheng; Song Wang; Xiaoyuan Yuan; Jiaqiang Wu; Zhijun Yu (Brazilian Journal of Microbiology, 2023)

Will the southward center of gravity migration of population, floor area, and building energy consumption facilitate building carbon emission reduction in China? - Rui Li; Kairui You; Weiguang Cai; Jiebing Wang; Yuan Liu; Yanhui Yu (Building and Environment, 2023)

Assessment of Chloride Salt Release Flux from Fluidized Cohesive Sediments in Quiescent Water - Jing Yuan; Binghui Zheng; Rui Wang; Minxi Zhang; Guoliang Yu (Water, Air, & Soil Pollution, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

High prevalence of vitamin D deficiency in Asia: A systematic review and meta-analysis - Zhiwei Jiang; Rui Pu; Na Li; Chaozhen Chen; Jialu Li; Wei Dai; Yuchen Wang; Jinxing Hu; Danji Zhu; Qiong Yu; Yuan Shi; Guoli Yang (Critical Reviews in Food Science and Nutrition, 2023)

In situ polymerization of polypyrrole in oil body for efficient solar-driven freshwater collection - Hongxiang Liu; Tianshu Zou; Xingyu Cui; Miao Ding; Biao Zhang; Xiaodong Yang; Yu Han; Shuwei Nie; Yuan Zhang; Enze Wang; Lili Wang; Yan Cheng; et al. (Chemical Engineering Journal, 2023)

Degradation of aflatoxins in apple juice by pulsed light and the analysis of their degradation products - Lige Qi; Yali Ma; Rui Cai; Yu Li; Ruinan Wang; Tianli Yue; Yahong Yuan; Zhenpeng Gao; Zhouli Wang (Food Control, 2023)

Screening of goaty flavor-inhibiting lactic acid bacteria and their effects on the flavor profiles of goat milk cakes - Huaixiang Tian; Rui Yang; Xuefeng Sun; Haiyan Yu; Juan Huang; Haibin Yuan; Xinman Lou; Zhaohu Yuan; Chen Chen (Food Bioscience, 2023)

Roles of vetiver roots in desiccation cracking and tensile strengths of near-surface lateritic soil - Qian-Feng Gao; Han Yu; Ling Zeng; Rui Zhang; Yuan-Hang Zhang (CATENA, 2023)

Driving forces and variation in water footprint before and after the COVID-19 lockdown in Fujian Province of China - Fan Yu; Yuan Wang; Xin Liu; Jinru Yu; Dandan Zhao; Haijun Deng; Bin Guo; Rui Shi; Bowei Wu; Huayang Chen (Journal of Cleaner Production, 2023)

Future land-use change and its impact on terrestrial ecosystem carbon pool evolution along the Silk Road under SDG scenarios - Min Cao; Ya Tian; Kai Wu; Min Chen; Yu Chen; Xue Hu; Zhongchang Sun; Lijun Zuo; Jian Lin; Lei Luo; Rui Zhu; Zhenci Xu; et al. (Science Bulletin, 2023)

Regulating the reaction pathway of nZVI to improve the decontamination performance through magnetic spatial confinement effect - Hai-Yuan Chi; Xiao-Xia Zhou; Min-Rong Wu; Wan-yu Shan; Jing-fu Liu; Jin-quan Wan; Bing Yan; Rui Liu (Journal of Hazardous Materials, 2023)

Interprovincial differences in the historical peak situation of building carbon emissions in China: Causes and enlightenments - Rui Li; Yanhui Yu; Weiguang Cai; Qiqi Liu; Yuan Liu; Haonan Zhou (Journal of Environmental Management, 2023)

Moderation device design for detecting hidden highly enriched uranium based on D-T neutron generator - Shang-Rui Jiang; Guang-Yu Shi; Si-Yuan Chen; Shi-Wei Jing; Chao Liu (Annals of Nuclear Energy, 2023)

High density mapping of wheat stripe rust resistance gene QYrXN3517-1BL using QTL mapping, BSE-Seq and candidate gene analysis - Shuo Huang; Yibo Zhang; Hui Ren; Xin Zhang; Rui Yu; Shengjie Liu; Qingdong Zeng; Qilin Wang; Fengping Yuan; Ravi P. Singh; Sridhar Bhavani; Jianhui Wu; et al. (Theoretical and Applied Genetics, 2023)

High cholesterol intake remodels cholesterol turnover and energy homeostasis in Nile tilapia (Oreochromis niloticus) - Rui-Xin Li; Ling-Yun Chen; Samwel M. Limbu; Yu-Cheng Qian; Wen-Hao Zhou; Li-Qiao Chen; Yuan Luo; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Marine Life Science & Technology, 2023)
The roles of dietary cholesterol in fish physiology are currently contradictory. The issue reflects the limited studies on the metabolic consequences of cholesterol intake in fish. The present study investigated the metabolic responses to high cholesterol intake in Nile tilapia ( Oreochromis niloticus ), which were fed with four cholesterol-contained diets (0.8, 1.6, 2.4 and 3.2%) and a control diet for eight weeks. All fish-fed cholesterol diets showed increased body weight, but accumulated cholesterol (the peak level was in the 1.6% cholesterol group). Then, we selected 1.6% cholesterol and control diets for further analysis. The high cholesterol diet impaired liver function and reduced mitochondria number in fish. Furthermore, high cholesterol intake triggered protective adaptation via (1) inhibiting endogenous cholesterol synthesis, (2) elevating the expression of genes related to cholesterol esterification and efflux, and (3) promoting chenodeoxycholic acid synthesis and efflux. Accordingly, high cholesterol intake reshaped the fish gut microbiome by increasing the abundance of Lactobacillus spp. and Mycobacterium spp., both of which are involved in cholesterol and/or bile acids catabolism. Moreover, high cholesterol intake inhibited lipid catabolic activities through mitochondrial β-oxidation, and lysosome-mediated lipophagy, and depressed insulin signaling sensitivity. Protein catabolism was elevated as a compulsory response to maintain energy homeostasis. Therefore, although high cholesterol intake promoted growth, it led to metabolic disorders in fish. For the first time, this study provides evidence for the systemic metabolic response to high cholesterol intake in fish. This knowledge contributes to an understanding of the metabolic syndromes caused by high cholesterol intake or deposition in fish.

Prediction of the Endocrine disruption profile of fluorinated biphenyls and analogues: An in silico study - Yuyan Zhong; Jing Ren; Rui Li; Yuxin Xuan; Wu Yao; Qianye Yang; Yin Gan; Shuling Yu; Jintao Yuan (Chemosphere, 2023)

Dietary sodium acetate improves high-fat diet utilization through promoting differential nutrients metabolism between liver and muscle in Nile tilapia (Oreochromis niloticus) - Wen-Hao Zhou; Samwel M. Limbu; Rui-Xin Li; Yuan Luo; Jiong Ren; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Aquaculture, 2023)

Antimicrobial activity and mechanism of preservatives against Alicyclobacillus acidoterrestris and its application in apple juice - Zhouli Wang; Yu Tian; Qi Wang; Tianmin Guo; Yahong Yuan; Tianli Yue; Hang Jia; Qian Ge; Zidan Zhao; Rui Cai (International Journal of Food Microbiology, 2023)

Development of a recombinant adenovirus-vectored vaccine against both infectious hematopoietic necrosis virus and infectious pancreatic necrosis virus in rainbow trout (Oncorhynchus mykiss) - Shouhu Li; Xincang Li; Rui Yuan; Xiaoxue Chen; Shouxu Chen; Yu Qiu; Qingfeng Yang; Meng Wang; Jiangao Shi; Shuo Zhang (Fish & Shellfish Immunology, 2023)

Interfacial modulation of organic-inorganic two-dimensional superlattices for efficient electromagnetic wave absorption - Wenjian Wang; Ke Ran; Xingwang Hou; Yilin Huang; Zidong Zhang; Dongxu He; Yuan Fang; Shuai Wang; Yu Liu; Rui Zhao; Xiao-Yu Yang; Weidong Xue (Chemical Engineering Journal, 2023)

Occurrence, correlation, and partitioning of organophosphate esters in soil and tree bark from a megacity, Western China - Can Wang; Rui-Yu Yuan; Shi-Qiang Wei; Ming-Jing He (Environmental Science and Pollution Research, 2023)

Monoterpenoid indole alkaloids with potential neuroprotective activities from the stems and leaves of Melodinus cochinchinensis - Yu-Jie Li; Juan Li; Lan Xie; Jun-Yu Zhou; Qiu-Xuan Li; Rui-Yuan Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2022)

Construction of a target MSNs drugcarrier loaded with siRNAGLI1 and siRNASMO aim at hedgehog signal pathway and the pharmacodynamic study of drug-carriers in the treatment of leukemia stem cells - Yuan Zhang; Rui Cai; HaiJun Li; Yu Duan; Yan Zhang; Wei Jing; ShaoGang Lv; Xi Chu; Zheng Cao; Lei Yang; Liang Ming (Drug Delivery and Translational Research, 2022)

Aluminum-activated Malate Transporter 12 is involved in restricting root-to-shoot Cl− transport in Arabidopsis under Cl−-salt stress - Rui-Wen Liu; Jian-Zhen Yuan; Xiao-Yu Li; Yan-Nong Cui; Mei-Mei Cai; Zi-Hua He; Qing Ma (Plant and Soil, 2022)

The effects of dietary fermented wheat bran polysaccharides on mucosal and serum immune parameters, hepatopancreas antioxidant indicators, and immune-related gene expression of common carp (Cyprinus carpio) juveniles - Rui-Fang Wang; Yuan Wang; Jun Zhang; Mei-Qi Weng; Yu-Hui Liu; Qiu-Yan Cheng; Min Song; Yan-Ping Yang; Xiao-Ping An; Jing-Wei Qi (Aquaculture International, 2022)

Application of nanostructures as antimicrobials in the control of foodborne pathogen - Yu Tian; Rui Cai; Tianli Yue; Zhenpeng Gao; Yahong Yuan; Zhouli Wang (Critical Reviews in Food Science and Nutrition, 2022)

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

Study on mechanical properties and damage mechanism of strongly weathered gneiss under freeze–thaw cycles - Xianghui Deng; Yu Zhang; Rui Wang; Dongyang Yuan (Arabian Journal of Geosciences, 2022)

Secondary metabolites isolated from Agrimonia pilosa Ledeb. - Hong-Rui Li; Yu-Kui Li; Jian Xiao; Cui Yang; Meng-Yuan Jiang; Kai Tian; Wei Wang; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2022)

The Identification and Prediction of Mesoscale Eddy Variation via Memory in Memory With Scheduled Sampling for Sea Level Anomaly - Rui Nian; Yu Cai; Zhengguang Zhang; Hui He; Jingyu Wu; Qiang Yuan; Xue Geng; Yuqi Qian; Hua Yang; Bo He (Frontiers in Marine Science, 2021)
Ocean mesoscale eddies are ubiquitous in world ocean and account for 90% oceanic kinetic energy, which dominate the upper ocean flow field. Accurately predicting the variation of ocean mesoscale eddies is the key to understand the oceanic flow field and circulation system. In this article, we propose to make an initial attempt to explore spatio-temporal predictability of mesoscale eddies, employing deep learning architecture, which primarily establishes Memory In Memory (MIM) for sea level anomaly (SLA) prediction, combined with the existing mesoscale eddy detection. Oriented to the western Pacific ocean (125°−137.5°E and 15°−27.5°N), we quantitatively investigate the historic daily SLA variability at a 0.25° spatial resolution from 2000 to 2018, derived by satellite altimetry. We develop the enhanced MIM prediction strategies, equipped with Gated Recurrent Unit (GRU) and spatial attention module, in a scheduled sampling manner, which overcomes the gradient vanishing and complements to strengthen spatio-temporal features for long-term dependencies. At the early stage, the real value SLA input guides the model training process for initialization, while the scheduled sampling intentionally feeds the newly predicted value, to resolve the distribution inconsistency of inference. It has been demonstrated in our experiment results that our proposed prediction scheme outperformed the state-of-art approaches for SLA time series, with MAPE, RMSE of the 14-day prediction duration, respectively, 5.1%, 0.023 m on average, even up to 4.6%, 0.018 m for the effective sub-regions, compared to 19.8%, 0.086 m in ConvLSTM and 8.3%, 0.040 m in original MIM, which greatly facilitated the mesoscale eddy prediction. This proposed scheme will be beneficial to understand of the underlying dynamical mechanism behind the predictability of mesoscale eddies in the future, and help the deployment of ARGO, glider, AUV and other observational platforms.

A multi-dosing regimen to enhance the spatial memory of normal rats with α5-containing GABAA receptor negative allosteric modulator L-655,708 - Congcong Yuan; An Gao; Qiang Xu; Beibei Zhang; Rui Xue; Yan Dou; Chunshui Yu (Psychopharmacology, 2021)

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Loganin ameliorates depression-like behaviors of mice via modulation of serotoninergic system - Chen-Hao Pan; Cong-Yuan Xia; Yu Yan; Yan Han; Rui Shi; Jun He; Ze-Xing Wang; Yu-Ming Wang; Wei-Ku Zhang; Jie-Kun Xu (Psychopharmacology, 2021)

Cyclic response of monopile-supported offshore wind turbines under wind and wave loading in sand - Rui Liang; Yu Yuan; Dengfeng Fu; Run Liu (Marine Georesources & Geotechnology, 2021)

Gastrodin Regulates the Notch Signaling Pathway and Sirt3 in Activated Microglia in Cerebral Hypoxic-Ischemia Neonatal Rats and in Activated BV-2 Microglia - Jing Guo; Xiao-Li-Na Zhang; Zhang-Rui Bao; Xue-Ke Yang; Ling-Shuang Li; Yu Zi; Fan Li; Chun-Yun Wu; Juan-Juan Li; Yun Yuan (NeuroMolecular Medicine, 2021)

The mTOR/NF-κB Pathway Mediates Neuroinflammation and Synaptic Plasticity in Diabetic Encephalopathy - Ting Xu; Jiao Liu; Xin-rui Li; Yinghua Yu; Xuan Luo; Xian Zheng; Yuan Cheng; Pei-quan Yu; Yi Liu (Molecular Neurobiology, 2021)

Tamlana haliotis sp. nov., isolated from the gut of the abalone Haliotis rubra - Wen-Rui Cao; Bang-Tao Liu; Xun-Ke Sun; Yuan-Yuan Sun; Ming-Yu Jiang; Zong-Jun Du (Archives of Microbiology, 2021)

Overexpression of T-type calcium channel Cav3.1 in oral squamous cell carcinoma: association with proliferation and anti-apoptotic activity - Rui-Fang Li; Qi-Wen Man; Jin-Yuan Liu; Yue-Yu Zheng; Xin Gao; Hai-Ming Liu (Journal of Molecular Histology, 2021)

Ruegeria haliotis sp. nov., Isolated from the Gut of the Abalone Haliotis rubra - Wen-Rui Cao; Dan-Dan Shang; Bang-Tao Liu; Yi-Hao Hu; Xun-Ke Sun; Yuan-Yuan Sun; Ming-Yu Jiang; Zong-Jun Du (Current Microbiology, 2021)

New titanite U–Pb and molybdenite Re–Os ages for a hydrothermal vein-type Cu deposit in the Lanping Basin, Yunnan, SW China: constraints on regional metallogeny and implications for exploration - Juan Li; Lei-Luo Xu; Xian-Wu Bi; Yong-Yong Tang; Xiang-Yuan Sheng; Hai-Jun Yu; Gong Liu; Rui Ma (Mineralium Deposita, 2021)

Prevalence of Clonorchis sinensis infection in fish in South‐East Asia: A systematic review and meta‐analysis - Ying Zhang; Qing‐Long Gong; Qing‐Bo Lv; Yang‐Yuan Qiu; Yan‐Chun Wang; Hong‐Yu Qiu; Xin‐Rui Guo; Jun‐Feng Gao; Qiao‐Cheng Chang; Chun‐Ren Wang (Journal of Fish Diseases, 2020)
Clonorchis sinensis , an important fish‐borne zoonotic trematode, is widely distributed in South‐East Asia, especially in China. Infections from human and animal reservoir hosts occur due to the consumption of raw or undercooked fish with C. sinensis metacercariae. This study aimed to evaluate the prevalence of C. sinensis metacercariae in fish in South‐East Asia via systematic review and meta‐analysis. We searched PubMed, ScienceDirect, China National Knowledge Infrastructure, Wanfang and Chongqing VIP databases for studies published between 1976 and 2020 that are related to the prevalence of C. sinensis metacercariae in fish. Studies were screened with keywords based on inclusion and exclusion criteria. Seventy‐one eligible articles were identified, covering three countries: China, Korea and Vietnam. The pooled prevalence of C. sinensis metacercariae in fish from South‐East Asia was 30.5%, with 35.1% in China, 29.7% in Korea and 8.4% in Vietnam. In subgroup analyses of climate, season, water source and publication date, the highest prevalence was identified in the Dwb climate type (43.3%), summer (70.2%), river (34.5%) and pre‐2001 publications (38.9%), respectively. In comparison, the lowest prevalence was found in the Dfa climate type (14.5%), winter (19.5%), lake (8.0%) and post‐2001 publications (23.8%). Meta‐regression results indicated that country ( p = .009), the published time ( p = .035) and water source subgroups ( p = .003) may be the source of heterogeneity. Overall, our study indicates that a high prevalence of C. sinensis infections occurs in fish in China, Korea and Vietnam, illuminating a significant public health concern in these countries.

The abscisic acid receptor gene VvPYL4 positively regulates grapevine resistance to Plasmopara viticola - Li Liu; Chang-Yuan Liu; Hui Wang; Shu-Yi Yu; Tian-Shu Guan; Yu-Fei Huang; Rui-Chun Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Ablation of olfactory bulb glutamatergic neurons induces depressive-like behaviors and sleep disturbances in mice - Mao-Yun Yuan; Ze-Ka Chen; Jian Ni; Tian-Xiao Wang; Shi-Yu Jiang; Hui Dong; Wei-Min Qu; Zhi-Li Huang; Rui-Xi Li (Psychopharmacology, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Enhancement of the activity of Cu/TiO2 catalyst by Eu modification for selective catalytic reduction of NOx with NH3 - Yuan-zhen Liu; Qi-yan Xu; Rui-tang Guo; Chao-peng Duan; Gui-lin Wu; Yu-fang Miao; Jing-wen Gu (Environmental Science and Pollution Research, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Crystal structure of impurity-free rhodochrosite (MnCO3) and thermal expansion properties - Wen Liang; Lin Li; Rui Li; Yuan Yin; Zeming Li; Xiqiang Liu; Shuangmin Shan; Yu He; Yong Meng; Zengsheng Li; Heping Li (Physics and Chemistry of Minerals, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

QTL mapping and genetic effect of chromosome segment substitution lines with excellent fiber quality from Gossypium hirsutum × Gossypium barbadense - Shao-qi Li; Ai-ying Liu; Ling-lei Kong; Ju-wu Gong; Jun-wen Li; Wan-kui Gong; Quan-wei Lu; Peng-tao Li; Qun Ge; Hai-hong Shang; Xiang-hui Xiao; Rui-xian Liu; et al. (Molecular Genetics and Genomics, 2019)

Crystal structure of norsethite-type BaMn(CO3)2 and its pressure-induced transition investigated by Raman spectroscopy - Wen Liang; Lin Li; Yuan Yin; Rui Li; Zeming Li; Xiqiang Liu; Chaoshuai Zhao; Shuguang Yang; Yong Meng; Zengsheng Li; Yu He; Heping Li (Physics and Chemistry of Minerals, 2019)

Complete mitochondrial genome of a kind of snakehead fish Channa siamensis and its phylogenetic consideration - Rui Li; Gang Wang; Zheng-Yong Wen; Yuan-Chao Zou; Chuan-Jie Qin; Yu Luo; Jun Wang; Gui-Hong Chen (Genes & Genomics, 2019)

MiR-429 improved the hypoxia tolerance of human amniotic cells by targeting HIF-1α - Lihao Ge; Yuyan Wang; Yang Cao; Gang Li; Rui Sun; Peng Teng; Yansong Wang; Yunlong Bi; Zhanpeng Guo; Yajiang Yuan; Deshui Yu (Biotechnology Letters, 2018)

Single crystal growth, crystalline structure investigation and high-pressure behavior of impurity-free siderite (FeCO3) - Wen Liang; Yuan Yin; Zeming Li; Rui Li; Lin Li; Yu He; Haini Dong; Zengsheng Li; Shuai Yan; Shuangmeng Zhai; Heping Li (Physics and Chemistry of Minerals, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Effects of diurnal temperature range on mortality in Hefei city, China - Jing Tang; Chang-chun Xiao; Yu-rong Li; Jun-qing Zhang; Hao-yuan Zhai; Xi-ya Geng; Rui Ding; Jin-xia Zhai (International Journal of Biometeorology, 2018)

Single crystal growth, characterization and high-pressure Raman spectroscopy of impurity-free magnesite (MgCO3) - Wen Liang; Zeming Li; Yuan Yin; Rui Li; Lin Chen; Yu He; Haini Dong; Lidong Dai; Heping Li (Physics and Chemistry of Minerals, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Different behavioral, neural and neuropeptide responses of fathers to their own and to alien pups in mandarin voles - Wei Yuan; Xiang-Ping Yang; Peng Yu; Rui Jia; Fa-Dao Tai; Bin Wei; Xiao Liu; Lei-Ge Ma (Journal of Comparative Physiology A, 2018)

Nominal effective immunoreaction volume of magnetic beads at single bead level - Rui Wang; Yuan Chen; Kai Fan; Feng Ji; Jian Wu; Yong-hua Yu (Journal of Zhejiang University-SCIENCE B, 2017)

Endothelial Progenitor Cells’ Classification and Application in Neurological Diseases - Jing-jing Yuan; Jing Yang; Shi-lei Sun; Rui Zhang; Yu-ming Xu (Tissue Engineering and Regenerative Medicine, 2017)

IP-10/CXCR3 Axis Promotes the Proliferation of Vascular Smooth Muscle Cells through ERK1/2/CREB Signaling Pathway - Hui-jin Wang; Yu Zhou; Rui-ming Liu; Yuan-sen Qin; Ying-huan Cen; Ling-yu Hu; Shen-ming Wang; Zuo-jun Hu (Cell Biochemistry and Biophysics, 2017)

Blood Flow and Oxygen Transport in Descending Branch of Lateral Femoral Circumflex Arteries After Transfemoral Amputation: A Numerical Study - Fei Yan; Wen-Tao Jiang; Rui-Qi Dong; Qing-Yuan Wang; Yu-Bo Fan; Ming Zhang (Journal of Medical and Biological Engineering, 2017)

Effects of short-term inflammatory and/or hypoxic pretreatments on periodontal ligament stem cells: in vitro and in vivo studies - Yang Yu; Chun-Sheng Bi; Rui-Xin Wu; Yuan Yin; Xi-Yu Zhang; Ping-Heng Lan; Fa-Ming Chen (Cell and Tissue Research, 2016)

Characterization and expression analyses of the H+-pyrophosphatase gene in rye - CHANG-SHUI WANG; QIAN-TAO JIANG; JIAN MA; XIU-YING WANG; JI-RUI WANG; GUO-YUE CHEN; PENG-FEI QI; YUAN-YING PENG; XIU-JIN LAN; YOU-LIANG ZHENG; YU-MING WEI (Journal of Genetics, 2016)

High-level expression of a novel recombinant human plasminogen activator (rhPA) in the milk of transgenic rabbits and its thrombolytic bioactivity in vitro - Shaozheng Song; Xin Ge; Yaobin Cheng; Rui Lu; Ting Zhang; Baoli Yu; Xueqiao Ji; Zhengqiang Qi; Yao Rong; Yuguo Yuan; Yong Cheng (Molecular Biology Reports, 2016)

Systematic Review by Multivariate Meta-analyses on the Possible Role of Tumor Necrosis Factor-α Gene Polymorphisms in Association with Ischemic Stroke - Yu-Ming Niu; Hong Weng; Chao Zhang; Rui-Xia Yuan; Jin-Zhu Yan; Xiang-Yu Meng; Jie Luo (NeuroMolecular Medicine, 2015)

New Perspectives on Dietary-derived Treatments and Food Safety—Antinomy in a New Era - Si-Yuan Pan; Si-Hua Gao; Rui-Chao Lin; Shu-Feng Zhou; Hong-Guan Dong; Min-Ke Tang; Zhi-Ling Yu; Kam-Ming Ko (Critical Reviews in Food Science and Nutrition, 2015)

Regulation of three isoforms of SOD gene by environmental stresses in citrus red mite, Panonychus citri - Ying-Cai Feng; Chong-Yu Liao; Wen-Kai Xia; Xuan-Zhao Jiang; Feng Shang; Guo-Rui Yuan; Jin-Jun Wang (Experimental and Applied Acarology, 2015)

Quantitative trait locus mapping for seed dormancy in different post-ripening stages in a Tibetan semi-wild wheat (Triticum aestivum ssp. tibetanum Shao) - Yun-Feng Jiang; Ji-Rui Wang; Wei Luo; Yu-Ming Wei; Peng-Fei Qi; Ya-Xi Liu; Qian-Tao Jiang; Yuan-Ying Peng; Guo-Yue Chen; Shou-Fen Dai; You-Liang Zheng; Xiu-Jin Lan (Euphytica, 2015)

Molecular cloning and functional analysis of a blue light receptor gene MdCRY2 from apple (Malus domestica) - Yuan-Yuan Li; Ke Mao; Cheng Zhao; Xian-Yan Zhao; Rui-Fen Zhang; Hua-Lei Zhang; Huai-Rui Shu; Yu-Jin Hao (Plant Cell Reports, 2013)

Postconditioning with vagal stimulation attenuates local and systemic inflammatory responses to myocardial ischemia reperfusion injury in rats - Qiang Wang; Yi Cheng; Fu-Shan Xue; Yu-Jing Yuan; Jun Xiong; Rui-Ping Li; Xu Liao; Jian-Hua Liu (Inflammation Research, 2012)

Does glyphosate impact on Cu uptake by, and toxicity to, the earthworm Eisenia fetida? - Chui-Fan Zhou; Yu-Jun Wang; Yuan-Chun Yu; Rui-Juan Sun; Xiang-Dong Zhu; Hai-Lin Zhang; Dong-Mei Zhou (Ecotoxicology, 2012)

CSMD1 exhibits antitumor activity in A375 melanoma cells through activation of the Smad pathway - Ming-Rui Tang; Yu-Xin Wang; Shu Guo; Si-Yuan Han; Di Wang (Apoptosis, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Comparative ecophysiological responses to drought of two shrub and four tree species from karst habitats of southwestern China - Chang-Cheng Liu; Yu-Guo Liu; Ke Guo; Guo-Qing Li; Yuan-Run Zheng; Li-Fei Yu; Rui Yang (Trees, 2011)

Comparison of sociability, parental care and central estrogen receptor alpha expression between two populations of mandarin voles (Microtus mandarinus) - Ruiyong Wu; Aifang Yuan; Qinwei Yuan; Rui Guo; Fadao Tai; Zhenzhen Song; Chengjun Yu (Journal of Comparative Physiology A, 2011)

Bacterial communities in PAH contaminated soils at an electronic-waste processing center in China - Wen Zhang; Hui Wang; Rui Zhang; Xie-Zhi Yu; Pei-Yuan Qian; M. H. Wong (Ecotoxicology, 2010)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Response spectrum analysis for non-classically damped linear system with multiple-support excitations - Rui-Fang Yu; Xi-Yuan Zhou (Bulletin of Earthquake Engineering, 2008)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)